IV Report of FLACSO's General Secretary: Integration in Latin America: actions and omissions, conflicts and cooperation - Rojas Aravena, Francisco (2009)
Integration is a means to reach political, economic, social and cultural goals. It is a road that ought to make possible the conditions for international insertion, in order to broaden and consolidate development, granting it sustainability, improving the wellbeing of the population and consolidating stability and peace. The above means that integration needs to build on a strategic political project. The essential basis for this is to be able to think and feel in a shared manner, in order to build a common voice in substantial areas that will make it possible to reach the goals indicated above. In this process, the national and regional leadership of governmental actors, of the civil society, of businesspeople, of intellectual communities, fulfill an irreplaceable role in leading processes and orienting actions to attain the proposed goals. In this paper I am examining the recent evolution of Latin American integration processes and their linkages with the major economic centers in the globe.